Advances in Two-Dimensional MXenes for Nitrogen Electrocatalytic Reduction to Ammonia - Lan-lan Yu; Jiang-zhou Qin; Wen-jun Zhao; Zhi-guang Zhang; Jun Ke; Bao-jun Liu (International Journal of Photoenergy)
As an important chemical raw material, ammonia is mainly produced by the traditional Haber-Bosch process, which has certain limitations such as high energy consumption, high safety responsibility, and severe pollution, thereby having negative impacts on ecosystem. The synthesis of ammonia from dinitrogen at ambient temperature and pressure is one of the most attractive topics in the field of chemistry. As a new two-dimensional nanomaterial, MXene has excellent electrochemical properties and is a potential catalytic material for electrocatalytic nitrogen fixation. In this review, we firstly introduce the crystal, electronic structures of two-dimensional MXenes and summarize the synthesis methods, N2 reduction, and simulation computation, as well as have insight into the challenges of MXenes, which shed light on the development of highly efficient MXene-based electrocatalysts in the reduction of N2 to ammonia.